P-16 Are we there yet? A survey of implementation progress against victoria's advance care planning strategy. (1st September 2015) - Doran, N; Detering, K; Austin-Crowe, Z
Abstract : Background: Advance care planning: have the conversation; A strategy for Victorian health services (2014 – 2018 ) promotes consistent practice and informs the development of processes, policies, guidelines, training and quality structures that support advance care planning (ACP). Four priority action areas are articulated with associated measures and timelines for implementation. Aim: A baseline survey of Victorian publicly funded health services has been conducted to: Determine the extent to which ACP is currently occurring Identify existing resources being used to support this; and Inform development of future resources to improve ACP access and uptake. Methods: The survey was administered to 84 Victorian publicly funded health services using the on-line survey tool. The questions were either single or multiple select option, and open-ended qualitative questions. Quantitative data were analysed using descriptive statistics and SPSS for Windows. Qualitative responses were independently categorised. Results: The survey achieved a 93% response rate. Baseline data shows that health services across Victoria are at varying stages of embedding ACP. A large proportion of health services are well progressed with implementing the measures and are perhaps exceeding year one expectations. Discussion: The strategy's implementation science approach focuses health services on the year one measures – building organisation wide implementation and developing systems and processes that will support sustained ACP. Conclusion: Survey results are assisting the Department to better understand what is enabling or impeding ACP implementation and identifying what would assist implementation. It provides a baseline for measuring implementation progress over the four years of the strategy.